2012
DOI: 10.1097/wox.0b013e31825a72fc
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Different Combined Regimens in the Treatment of Cholinergic Urticaria

Abstract: BackgroundCholinergic urticaria is uncommon and accounts for 10% of all young adults. To date, there is no effective therapy for cholinergic urticaria.ObjectiveTo determine the therapeutic efficacy of different drug combinations in the treatment of cholinergic urticaria.Patients and MethodsThe participants included in the study are in the age range of 16 to 29 years, with cholinergic urticaria of any duration as diagnosed by physicians. Patients were recruited from Asthma and Allergy Centers in Baghdad and Tik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
0
7
0
2
Order By: Relevance
“…Four studies including 316 patients assessed antihistamines for the treatment of cholinergic urticaria. [35][36][37][38]41 First-generation H1-AHs versus second-generation H1-AHs versus placebo. Kobza Black et al 36 used 20 mg of hydroxyzine 3 times daily versus placebo and found that the mean "degree of improvement'' (self-assessed; scale: minimal 5 0, maximal 5 3) was 1.58 (n 5 10) for hydroxyzine and 0.74 (n 5 9) for placebo after 5 days of treatment.…”
Section: Cholinergic Urticariamentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies including 316 patients assessed antihistamines for the treatment of cholinergic urticaria. [35][36][37][38]41 First-generation H1-AHs versus second-generation H1-AHs versus placebo. Kobza Black et al 36 used 20 mg of hydroxyzine 3 times daily versus placebo and found that the mean "degree of improvement'' (self-assessed; scale: minimal 5 0, maximal 5 3) was 1.58 (n 5 10) for hydroxyzine and 0.74 (n 5 9) for placebo after 5 days of treatment.…”
Section: Cholinergic Urticariamentioning
confidence: 99%
“…First-generation H1-AHs in combination. Alsamarai et al 35 recruited a total of 251 patients and compared 3 groups: 4 mg of chlorpheniramine maleate (half hour before exercise) plus 5 mg of chlordiazepoxide plus 2.5 mg of clindium bromide 3 times daily versus 4 mg of chlorpheniramine maleate 3 times daily plus 25 mg of maprotiline HCL once daily versus 4 mg of chlorpheniramine maleate 3 times daily plus 20 mg of cimetidine 3 times daily. Pairwise comparisons of all 3 groups showed that adding maprotiline was more effective than adding chlordiazepoxide and clindium bromide (RR, 0.32; 95% CI, 0.21-0.48), as was adding cimetidine (RR, 0.28; 95% CI, 0.19-0.42) when evaluating "complete symptom control.''…”
Section: Cholinergic Urticariamentioning
confidence: 99%
“…Although oral antihistamines are a primary treatment for ChU, some patients do not respond successfully to antihistamine therapy . In this study, most patients showed at least partial improvement with oral antihistamines.…”
Section: Discussionmentioning
confidence: 64%
“…Histamine H 1 -receptors play a major role in the pathogenesis of extrinsic asthma, and blockade of this receptor is well-known to protect against asthmatic attacks [58,59,60]. Moreover, calcium channel blockade in bronchial tree was reported to decrease airway remodeling [16], while inhibition of calcium influx into mast cells decreases their ability for degranulation and histamine release [49].…”
Section: Discussionmentioning
confidence: 99%